ANSWERING THE CUSTOMER SATISFACTION “KONGKOW” CAFÉ PLACE IN SURABAYA - Asmara Indahingwati (Fakultas Ekonomi Universitas 45 Surabaya, 2017)
This study examines the effect of price on customer satisfaction Cafe in Surabaya, by reviewing the factor price, promotion, and quality of service to customer satisfaction. The study population is a consumer in Cafe Oost Koffie & Thee in Surabaya, with accidental sampling technique was taken by 100 respondents. Analysis of date through multiple linear regression test obtained F = 185 823; p = 0.000 p (<0.05); which means that the factor price, promotion, and service quality effect on customer satisfaction. The coefficient of determination shows pricing, promotions, and service quality of a contribution of 85.3% on customer satisfaction. Testing hypotheses about the effect of price on customer satisfaction obtained by value t = 1.152; p = 0.124 (p> 0.05) means that the effect of price does not affect the customer satisfaction; promotional effect on customer satisfaction obtained t = 6.210; p = 0.000 (p <0.05), the promotion proved no effect on customer satisfaction; and impact of service quality on customer satisfaction obtained t = 1.769; p = 0.080 (p> 0.05), the quality of service is not proven effect on customer satisfaction.